# Using appropriate properties find the value of given expression . $\frac{-2}{3}\times\frac{3}{5}+\frac{5}{2}-\frac{3}{5}\times\frac{1}{6}$.

Given :

$\frac{-2}{3} \times \frac{3}{5} + \frac{5}{2} - \frac{3}{5} \times \frac{1}{6}$

To Find :

We have to find the value of the given expression.

Solution :

Distributive Property:

The distributive property of multiplication states that when a factor is multiplied by the sum or difference of two terms, it is essential to multiply each of the two numbers by the factor, and finally perform the addition or subtraction operation.

This property is symbolically stated as:

$a (b+c) = a\times b + a\times c$

$a (b-c) = a\times b - a\times c$

Therefore,

$\frac{-2}{3} \times \frac{3}{5} + \frac{5}{2} - \frac{3}{5} \times \frac{1}{6}=\frac{-2}{3} \times \frac{3}{5} - \frac{3}{5} \times \frac{1}{6} + \frac{5}{2}$

$= \frac{-3}{5} (\frac{2}{3} + \frac{1}{6}) + \frac{5}{2}$

$=\displaystyle \frac{-3}{5} \ \times \ \frac{2\times 2+1}{6} \ +\ \frac{5}{2}$

$= \frac{-3}{5}\times \frac{5}{6} + \frac{5}{2}$

$= \frac{-1}{1}\times\frac{1}{2} + \frac{5}{2}$

$= \frac{-1}{2} + \frac{5}{2}$

$= \frac{5-1}{2}$

$= \frac{4}{2}$

$= 2$.

$\frac{-2}{3} \times \frac{3}{5} + \frac{5}{2} - \frac{3}{5} \times \frac{1}{6}$ = 2

Updated on: 10-Oct-2022

24 Views 